FEATURES OF EMOTIONAL BURNOUT OF WORKER IT SECTOR AS REPRESENTATIVES OF PROFESSIONS OF SUBJECT-OBJECT TYPE (Psychology Travelogs, 2021)
The article discusses the problem of emotional burnout of employees of the subject-object type. Particular attention is paid to IT workers, as this industry is constantly evolving and the demand for quality professionals is growing in all parts of the world. During the pandemic, an even higher percentage of "burned out" members of this profession were identified. The article analyzes the different views of researchers on the issue of emotional burnout in the professions of the "non-social sphere". Our aim with this paper was analysis of the specifics of emotional burnout of IT-workers, as representatives of the subject-object type of professions, and development of recommendations for minimizing organizational factors that can cause emotional burnout.The main content of the study includes the analysis of the concept of "emotional burnout". Burnout is one such widely acknowledged stress outcome. Burnout can be characterized by a three factor model: a degree of emotional exhaustion, depersonalization in dealings with the recipients of one’s services and a lack of sense of personal accomplishment Some scholars hold different views as to which component is more pronounced in subject-object professions: emotional exhaustion or depersonalization.The main differences between burnout in subject-subject professions and subject-object professions are highlighted. Much attention is given to the factors that can cause emotional burnout.The article presents the characteristic stressful factors of professional activity of IT specialists, which can have a serious impact on the formation of emotional burnout. Based on this, recommendations is proposed to improve organizational policies among IT companies, which can reduce the risk of this condition in their employees.
Keywords: emotional burnout; components of emotional burnout; factors of emotional burnout; subject-object professions